2017
DOI: 10.1016/j.jid.2016.09.032
|View full text |Cite
|
Sign up to set email alerts
|

A PLEC Isoform Identified in Skin, Muscle, and Heart

Abstract: mediated by antibodies against thymusindependent carbohydrate antigen, for example, mismatched ABO antigen, and activated macrophages (Takahashi, 2005). Our HF allograft model is suitable for transplantation research, relatively easy to evaluate and more applicable to clinical studies, unlike solid organ transplantation. We found that MD-3 pretreatment enhanced HF allograft survival by significantly reducing alloreactive T-cell infiltration. The induction of antigen-specific T-cell tolerance by MD-3 could be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…This work was the first report indicating that life-threatening cardiac disease manifestations may occur before the onset of skeletal muscle symptoms, underscoring the importance of routine cardiological evaluation including electrophysiological and cardiac imaging studies that should be part of the diagnostic work-up of all EBS-MD and EBS-MD-MyS patients. This is also in line with another study, in which a family with several cases of fatal cardiomyopathy was reported, and PLEC mutations were finally identified for the index patient [ 25 ]. Recently, out of a family with three siblings suffering from LGMDR17 due to a mutation in exon 1f, one patient died from sudden cardiac death after spontaneous pneumothorax [ 16 ].…”
Section: Clinical Phenotypes and Muscle-related Disease Manifestations Of Human Plectinopathiessupporting
confidence: 90%
See 1 more Smart Citation
“…This work was the first report indicating that life-threatening cardiac disease manifestations may occur before the onset of skeletal muscle symptoms, underscoring the importance of routine cardiological evaluation including electrophysiological and cardiac imaging studies that should be part of the diagnostic work-up of all EBS-MD and EBS-MD-MyS patients. This is also in line with another study, in which a family with several cases of fatal cardiomyopathy was reported, and PLEC mutations were finally identified for the index patient [ 25 ]. Recently, out of a family with three siblings suffering from LGMDR17 due to a mutation in exon 1f, one patient died from sudden cardiac death after spontaneous pneumothorax [ 16 ].…”
Section: Clinical Phenotypes and Muscle-related Disease Manifestations Of Human Plectinopathiessupporting
confidence: 90%
“…Blood serum creatine kinase (CK) levels have been reported for five EBS-MD cases, with two patients showing normal and three showing increased values [ 18 , 19 , 20 , 21 , 22 ]. Electromyography (EMG) in EBS-MD patients revealed a myopathic pattern with short duration, polyphasic, and low-amplitude motor unit potentials [ 19 , 23 , 24 , 25 ]. Furthermore, fibrillation potentials, positive sharp waves, and pseudomyotonic/myotonic discharges have been reported, whereas nerve conduction and neuromuscular transmission appeared to be normal [ 19 ].…”
Section: Clinical Phenotypes and Muscle-related Disease Manifestations Of Human Plectinopathiesmentioning
confidence: 99%
“…Ген плектина локализован в 8q24.3 и состоит из 32 экзонов, при этом экзоны 2-32 являются константными, а первые 8 экзонов -альтернативными, соединяющимися в общий экзон 1. Особенности структуры гена определяют формирование 9 изоформ белка плектина (1, 1а, 1b, 1c, 1d, 1e, 1f, 1g, 3), образующихся вследствие альтернативного сплайсинга первого экзона [3][4][5].…”
Section: Introductionunclassified
“…Approximately 8% of patients with EBS are estimated to carry PLEC mutations (2). The PLEC gene encodes the large cytolinker protein plectin (3)(4)(5). Plectin mutations, inherited in an autosomal recessive pattern, result in distinct phenotypes, including EBS with muscular dystrophy (MD), EBS with pyloric atresia (PA) and EBS with skin lesions only (3,6).…”
mentioning
confidence: 99%
“…These findings were consistent with the diagnosis of EBS due to PLEC mutations. A custom-designed panel of EB-related genes was analysed by the Department of Medical Genetics in Warsaw, Poland, using VALARI 1 , Martha THEODORAKI 2 , Ierotheos LOUKAS 3 , Sylvia GKANTSEVA-PATSOURA 2 , Georgia KARAVANA 2 , Vasiliki FALAINA 2 , Lilia LYKOPOULOU 1 , Roser PONS 4 , Ioannis ATHANASIOU5 , Katarzyna WERTHEIM-TYSAROWSKA6 , Christina KANAKA-GANTENBEIN1 and Dimitra KIRITSI 5 * The patient is compound heterozygous for the novel mutation c.11912del, p.Lys3971ArgfsTer10 and the mutation c.12499C>T, p.Arg4167Ter, both located in exon 32 of the PLEC gene (name according to coding ref seq: NM_000445.3).…”
mentioning
confidence: 99%